Provinces Proven To Violations, Neutrality Of State Civil Apparatus In The 2024 General Election - Junaedi Junaedi (Badan Penerbit STIEPARI Press, 2024)
Neutrality of ASN and other state apparatus, so that the 2024 election will run with JURDIL (honest & fair), and LUBER (broad, general, free of secrets). The strengthening of ASN's non-neutrality in the 2024 elections is proven based on the latest Kurious Survey from Katadata Insight Center (KIC) showing that there are still many people who think that President Joko Widodo (Jokowi) is not serious about guarding the neutrality of the state civil apparatus or ASN in the 2024 Elections.This potential vulnerability was found in 22 Indonesian provinces. Of this number, 10 provinces have the highest vulnerability index for ASN neutrality violations, namely North Maluku with a score of 100 on a scale of 0-100. Scores, North Sulawesi is in second place, followed by Banten, South Sulawesi, NTT, East Kalimantan, West Java, West Sumatra, Gorontalo and Lampung.Cases of ASN Irregularities in the 2024 Election by Type of Violation (May-November 2023). The NGO Coalition for Election Justice (SINGKAP), consisting of KontraS, Setara Institute, Imparsial, and KPPOD, noted that there were 59 cases of alleged irregularities committed by State Civil Apparatus (ASN) ahead of the 2024 Election in the May-November 2023 period.According to the type, the most common cases found in ASN include: (1). State officials massively openly abuse the authority and resources inherent in them to act unfairly by favouring certain contestants; (2). Violations by village heads, Polri and service heads; (3). Neutrality violations, namely 32 cases; (4). There were 24 cases of election fraud and 4 cases of violations of professionalism; (5). ASN support for certain contestants (40 actions); official support for contestants (7 actions); as well as covert campaigns (4 actions);